DAMPAK MEDIA SOSIAL TERHADAP KESEHATAN MENTAL PADA SISWA SMP NEGERI 38 BEKASI - Saptura, Muhammad Iqbal; Supriatna, Ecep (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
The increased use of social media among adolescents affects the mental health of students at SMP Negeri 38 Bekasi. This study used quantitative methods with a sample of 102 students randomly selected from a population of 1,270 students. Data was collected through a questionnaire measuring social media use and mental health. The results of the Spearman correlation analysis showed a coefficient of 0.616 with a significance of 0.000 (sig < 0.05), and the Pearson correlation test showed a coefficient of 0.657 with a significance of 0.000 (sig < 0.05), indicating a significant positive relationship between the two variables. The higher the use of social media, the higher the level of student mental health. In conclusion, social media use has a positive effect on students' mental health at SMP Negeri 38 Bekasi. Suggestions include social media education programs in schools for healthy and wise use, as well as a holistic approach in supporting students' mental health. Peningkatan penggunaan media sosial di kalangan remaja mempengaruhi kesehatan mental siswa di SMP Negeri 38 Bekasi. Penelitian ini menggunakan metode kuantitatif dengan sampel 102 siswa yang dipilih acak dari populasi 1.270 siswa. Data dikumpulkan melalui kuesioner yang mengukur penggunaan media sosial dan kesehatan mental. Hasil analisis korelasi Spearman menunjukkan koefisien 0.616 dengan signifikansi 0.000 (sig < 0.05), dan uji korelasi Pearson menunjukkan koefisien 0.657 dengan signifikansi 0.000 (sig < 0.05), mengindikasikan hubungan positif signifikan antara kedua variabel. Semakin tinggi penggunaan media sosial, semakin tinggi tingkat kesehatan mental siswa. Kesimpulannya, penggunaan media sosial berpengaruh positif terhadap kesehatan mental siswa di SMP Negeri 38 Bekasi. Saran meliputi program edukasi media sosial di sekolah untuk penggunaan yang sehat dan bijak, serta pendekatan holistik dalam mendukung kesehatan mental siswa.